Risk Assessment Menggunakan Pendekatan Octave Allegro (Studi Kasus: Schoology.com) - Soetam Rizky Wicaksono; Cataryna Lenny Dwi Rizka; Gracecilla Aprillia Immanuel (Jurnal ICT : Information Communication & Technology, 2019)
Risk in information system, whether it is in desktop application or web commonly being ignored. Especially for public web which already having vast users. One of it is Schoology.com which has claimed themselves already having million of users. This research discussed about the risk assesment of information systems by using the Octave Allegro approach in in the form of a possibility threat that occur in the Schoology.com site. We choose the Octave Allegro because it one of agile, fast and has the ability to provide strong risk assessment results, with relatively small investments in time and resource even for organizations that do not have extensive risk management expertise. After doing the research, the main impact areas that found on the Schoology.com are reputation and customer confidence. The results show that the level on the Schoology site is a medium because, the data contained on this site is not too important so the possibility of being misused by foreigners can be considered small.